An analysis of item response theory using program R - Ali, Ali; Istiyono, Edi (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
The test is one of the instruments used to assess the extent of student understanding in learning. Multiple choice is a type of test commonly used in testing students. In addition to testing students' understanding, the quality of the tests used also needs to be tested. This study aims to determine the characteristics of the national mathematics test items in Baubau in the 2015/2016 academic year and the test information function with the item response theory approach. This research is an ex-post-facto study with a sample size of 574 students using a random sampling technique. Data was collected through documentation and analyzed using the LTM R package program. Findings indicated that there were four items (I1, I2, I4, and I8) for the 1-PL model, six items (I1, I2, I4, I7, I8, and I10) for the 2-PL model, and seven items (I1, I2, I3, I4, I7, I9, and I10) (3-PL) that fit the model (FM). The percentage of good (G) item parameters using R was 90% for (b) (1-PL), 90% (b) and 100% (a) (2-PL), and 90% (b), 10% (a), and 70% (c) (3-PL). The percentage of good quality items in each model for the 1-PL model was 40% or four items, the 2-PL model was 60% or six items, and the 3-PL model was 0%, or none was included in the good quality item category.